Implementation and Experiments on Face Detection System (FDS) Using Perceptual Quality Aware Features - Khan, Amir (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
This thesis is motivated by developing a face detection system for detecting faces in distorted images. Interaction between face detection and perceptual image quality is studied and analyzed to develop this robust face detection system. It is observed that accuracy of existing face detection systems are degraded with increase in distortion which is occurred due to many factors like low resolution of cameras, during transmission or storing. These types of distortions are AWGN, G Blur and JPEG. To overcome this problem, a new set of features named QUALHOG (which is a combination of NSS features and HOG features) is proposed for better and accurate face detection which augments Histogram of Oriented Gradients (HOG) features with perceptual quality-aware spatial Natural Scene Statistics (NSS) features. Face detection system based on QUALHOG features shows a great improvement in detecting faces as compared to face detection system based on HOG features. A large set of images are used for experimentation. To facilitate these experiments, a distorted face database (DFD) which contains face and non-face images by a variety of common distortion types and levels is used. This new dataset is available for download and further experimentation and it contains images at 10 distortion levels. Precision and Recall are calculated, Precision versus distortion level and Recall versus Distortion level curves are obtained to show the comparison between HOG and QUALHOG based face detection systems. Furthermore obtained results are compared with known results and presented as AUPR versus Distortion level curves to show the feasibility of FDS. Keywords: Face detection system, Distorted images, Perceptual Quality Aware features, Histogram of Oriented Gradients

ÖZ Bu tez, bozulmuş görüntülerde yüzleri tespit etmek için bir yüz algılama sistemi geliştirerek motive edilir. Yüz tanıma ve algılamalı görüntü kalitesi arasındaki etkileşim incelenmiş ve sağlam bir yüz tespit sistemi geliştirilmiştir. Mevcut yüz tanıma sistemlerinin doğruluğunun, kameralarda düşük çözünürlük, iletim veya depolama gibi pek çok faktöre bağlı olarak bozulma artışı ile bozulduğu gözlemlenmiştir. Bu tür bozulmaların sebebi AWGN, G Blur ve JPEG'tir. Bu sorunun üstesinden gelmek için, QUALHOG isminde yeni bir öznitelik kümesi önerilmiştir. Bu yöntem, NSS vs HOG özniteliklerini içermektedir. QUALHOG özniteliklerini temel alan yüz tanıma sistemi, HOG özniteliklerini kullanan yüz tanıma sistemi ile karşılaştırıldığında, HOG özniteliklerine göre yüz tanımada büyük bir gelişme olduğunu gösterir. Deneyler için geniş bir görüntü grubu kullanılmıstır. Bu deneyleri kolaylaştırmak için, çeşitli genel çarpıtma türleri ve seviyeleri ile yüz ve yüz olmayan görüntüler içeren çarpık bir yüz veritabanı (DFD) kullanılmıştır. Bu yeni veri kümesi, indirilebilir,ileriki deneyler için kullanılabilir ve 10 bozulma seviyesinde görüntüler içerir. Deneylerde, Hassas ve Geri Çağırma hesaplanmış, Hassas ve bozulma seviyesi, ve Geri Çağırma ve Çarpışma seviyesi eğrileri, HOG ve QUALHOG tabanlı yüz tanıma sistemleri arasındaki karşılaştırmayı göstermek için elde edilmiştir. Ayrıca elde edilen sonuçlar, bilinen sonuçlarla karşılaştırıldığında, FDS'nin fizibilitesini göstermek için AUPR ve Distorsiyon seviyesi eğrileri olarak gösterilmiştir. Anahtar Kelimeler: Yüzalgılamasistemi, Bozulmuş görüntüler, Algısal Kaliteye Duyarlı Öznitelikler, Odaklı Eğim Histogramı
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2017. Supervisor: Assoc. Prof. Dr. Alexander Chefranov.
Keywords: Computer Engineering; Computer Vision; Image Processing; Face detection system; Distorted images; Perceptual Quality Aware features; Histogram of Oriented Gradients